This action might not be possible to undo. Are you sure you want to continue?
First Order Linear Equations
The standard form for a first order linear differential equation is
y! + p(t)y = q(t)
where y! = dy / dt and p(t) and q(t) are any functions of t. Rearranging,
[ p(t)y ! q(t)] dt + dy = 0
which has the form M (t, y)dt + N(t, y)dy = 0 with
M (t, y) = p(t)y ! q(t),!!N(t, y) = 1
Equation (5.2) is not, in general, exact because M y = p(t) and N t = 0 ; exactness would require M y = N t or p(t) = 0 , in which case (5.1)reduces to y! = q(t) and the variables easily separate to give y =
! q(s)ds + C .
In the more general case, when p(t) ! 0 , we
look for an integrating factor. Since
(M t ! N t ) / 1 = [ p(t) ! 0] / 1 = p(t)
is only a function of t, an integrating factor is
µ (t) = e !t
Multiplying equation (5.2) by the integrating factor gives M (t, y)dt + N(t, y)dy = 0 where
M (t, y) = µ (t)p(t)y ! µ (t)q(t),!!N(t, y) = µ (t)
and a solution is ! (t, y) = C , where
!" !" = M (t, y) = µ (t)p(t)y # µ (t)q(t),!! = N(t, y) = µ (t) !t !y
© 2005 BE Shapiro
[Math 351 Spring 2005 revised 3/25/05]
9) From equation (5. The following constructive algorithm gives an alternative proof of (5.13) and is generally more useful for solving the general linear equation than memorization of the formula.11) Therefore h(t) = ! " µ (s)q(s)ds and by equation (5. y) = µ (t)y " # µ (s)q(s)ds = C t (5. Differentiating with respect to t and setting the result equal to the first of equations (5.5) we calculate µ !(t) = p(s)ds d "t p(s)ds e = p(t)e "t = p(t)µ (t) dt (5. THEOREM.7) !" dh = µ #(t)y + = µ (t)p(t)y $ µ (t)q(t) !t dt (5. The result is summarized in the following theorem.8) t ! (t. The one-parameter family of solutions to the general first order linear differential equation y! + p(t)y = q(t) is y= where µ (t) = e !t p(s)ds 1 " C + ! µ (s)q(s)ds $ # % t µ (t) (5.10) into (5.From the second of equations (5.10) Substituting (5. © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5.2 . ! (t.8) where h may depend on t but not on y.13) . y) = "y µ(t)dy + h(t) = µ(t)y + h(t) (5.12) is a solution of (5.1).9) and canceling like terms gives dh = ! µ (t)q(t) dt (5.7).
3 . Multiplying equation (5. An integrating factor is µ (t) = e !t p(s)ds = e !t 2sds = et . Example 1. To solve y! + p(t)y = q(t) (1) Compute µ (t) = e !t p(s)ds and observe that µ !(t) = p(t)µ (t) . Solve the differential equation y! + 2ty = t (5.14) This has the form y! + p(t)y = q(t) .16) Example 2. giving µ (t) y! + µ !(t)y = µ (t)q(t) . t (5) Divide by µ (t) to obtain equation (5. ! (1/t )dt Putting this into standard form gives y! " y / t = te"t . d [(1 / t)y ] = (1 / t)( y! " y / t) = te"t dt © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] (5. dt ! µ(s)q(s)ds .14) through by the integrating 2 factor 2 d ! t2 # t2 ye = e ( y% + 2ty) = tet $ dt " (5. µ (t)y = d [ µ (t)y ] = µ (t)q(t) .17) Page 5.15) Hence 2 2 2 2 '1 2 * 1 y = e!t # " ses ds % = e!t ) et + C . Multiplying throught. (3) Apply the product rule and observe from this that (4) Integrate over t. where p(t) = 2t and q(t) = t .ALGORITHM 1. ■ $ t & (2 + 2 (5.13). Hence µ = e " = e! ln t = 1 / t . Solve ty! " y = t 2 e"t . (2) Multiply the ODE through by µ (t) . = + Ce!t .
among them the following.Therefore y = t # " e!t dt % = C ! e!t . $ & (5. y(0) = 1 (5.24) © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5.18) Example 3. y(t 0 ) = y0 (5. Solve the initial value problem y! + y = cost.20) Integrating and solving for y.4 . D !1[ f (t)] = "t f (s)ds + C (5.22) The Linear Differential Operator D We write the general linear first order initial value problem in terms of the linear differential operator D = d / dt as [ D + p(t)] y = q(t) .21) The initial condition gives C = 1 / 2 and hence the solution of the initial value problem is y= 1 " cost + sin t + e!t $ . #1 & y = e!t " es cos s!ds = e!t % et (sin t + cost) + C ( t $2 ' (5. % 2# (5. Multiplying the differential equation through by the integrating factor gives d t ! e y # = et ( y% + y) = et cost dt " $ (5.23) The operator D has several useful properties.19) Since p(t) = 1 an integrating factor is µ = et .
Applying property (5.25) follows immediately from (5.25) (5.26) D " e !t $ # p(s)ds y % = e !t ' & p(s)ds [ D + p(t)] y (5.D[eat y] = eat (D + a)y D[e f (t ) y] = e f (t ) [D + f !(t)]y (5. Equation (5.30) which is identical to equation (5. To generalize to the initial value problem define the function t µ (t) = µ (t 0 )exp " ! p(s)ds % $ to ' # & (5. and equation (5.26).27) to (5. © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5.26) follows from the product rule for derivatives.26) with f (t) = at.13).27) Property (5.26) with p(t) any anti-derivative of f (t) .24) to (5.31) Then by (5.23) D " e !t $ # p(s)ds y % = e !t ' & p(s)ds q(t) (5. and property (5.5 .29) Hence the solution of (5.23) is ! p(s)ds # "s p(r)dr q(s)ds + C & y = e "t % "t e ( $ ' (5.28) ye !t p(s)ds p(s)ds & p(s)ds = D "1D # e !t y ( = D "1 # e !t q(t) & = % % ( $ ' $ ' !t e ! s p(r)dr q(s)ds + C (5.27) is a special case of (5.24) is the fundamental theorem of calculus (let f (t) = F !(t) and the result follows).28) Applying property (5.
23). theorem.34) Setting t = t 0 gives C = µ (t 0 )y0 .32) D [ µ (t)y ] = µ (t)q(t) and hence by (5.36) t where µ (t) = µ (t 0 )exp " ! p(s)ds % . y0 ) is (5. $ to ' # & The proof holds regardless of the choice of initial condition on µ (t) and hence we are free to set µ (t 0 ) = 1 . y) = q(t) ! p(t)y . (5.D[ µ (t)y] = µ (t)[D + p(t)]y Substituting (5. The unique solution to the initial value problem y! + p(t)y = q(t). then y= t 1 " y0 + ! µ (s)q(s)ds % ' t0 µ (t) $ # & (5.33) µ (t)y = C + ! µ (s)q(s)ds t0 t (5. This is equivalent to defining µ (t) = exp " ! p(s)ds $ where we # t % ignore the constant of integration. Then © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5. Hence we have derived the following existence THEOREM.35) y= t 1 " y0 µ (t 0 ) + ! µ (s)q(s)ds % ' t0 µ (t) $ # & (5. we observe that the differential equation can be written in the form y! = f (t.24) (5. y) where f (t.6 .37) Proof. To prove uniqueness. We have already demonstrated existence by deriving the solution.!y(t 0 ) = y0 where p(t) is a bounded function in some open neighborhood N of (t 0 .
f (t.40) Were it not for the factor of y n equation (5.43) © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5.40) would be linear. although they are not linear.36)B 0 t #1 + t e!2s e7s ds & = e2t #1 + 1 e5s & = e2t # 4 + 1 e5t & y=e % ( %5 5 ( % "0 ( $ ' $ ' % ( 0' $ 5 2t (5. and in fact it is linear if n = 0 or n = 1 . and have the form y! + p(t)y = y n q(t) (5. Bernoulli equations can be made linear by making the substitution z = y1! n (5.39) Bernoulli Equations These equations are similar in form to equation (5.1). and therefore y! = 1 n y z! 1"n (5. y2 ) = q(t) ! p(t)y1 ! q(t) + p(t)y2 = p(t) y1 ! y2 < M y1 ! y2 where M = sup N p(t) .41) Differentiating. Solve the initial value problem y! " 2y = e7t .7 . Hence f is Lipshitz and the solution is unique.38) t (5.42) where z! = dz / dt . y(0) = 1 An integrating factor is µ = exp " (!2)dt = e!2t . From equation (5. y1 ) ! f (t. z! = (1 " n)y "n y ! (5. Example 4. For any other value of n.
8 .47). and in standard from becomes z! + (1 " n)p(t)z = (1 " n)q(t) Example 5.50) An integrating factor is µ = e ! rearranging.48) into the original differential equation gives z! 4y Multiplying through by 4y 3 . 3 + ty = t y3 (5. Differentiating (5. 4t = e2t .Substituting (5.40) gives 1 n y z" + p(t)y = y n q(t) 1! n (5.41) 1 z" + p(t)z = q(t) 1! n (5.46) (5.50) through by µ and 2 © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5.48) Substituting (5.47) The initial condition is z(1) = [y(1)]4 = 2 4 = 16 . z! = 4y3 y! (5.43) into (5. so we let z = y1! n = y1!(!3) = y 4 (5.49) z! + 4tz = 4t (5. Solve y! + ty = t / y 3 .45) which is linear in the variable z.44) Dividing through by y n and using (5. Multiplying equation (5. y(1) = 2 This is a Bernoulli equation with n = -3.
2 2 d ! 2t 2 # ze = e2t ( z% + 4tz ) = 4te2t $ dt " (5.54) ans: y = ans: y = ans: y = C ! cost t3 (2) ty! + 2y = et . ze2t = 2 !t 4se2s ds = e2t + C 2 2 (5. t (8) t 2 y! + 2ty " y 3 = 0 ans: y = ± 5Ct 2C 2 ! t 5 © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5.9 . so that z = 1 + 15e2!2t 2 (5.!!y(" ) = 1 (6) y(1) = ! / 2 dy 1 + y = et y(a) = ya dt t (7) y! + n y = At " n . t <0 t ( 2 ) 1/4 (5. we find that C = 15e2 . t > 0 t t et (t ! 1) + C t2 sin t t2 (4) y! + 4t 3 y = t 3 .51) Integrating.!!y(0) = 1 (5) y! + y = sin t. t > 0 (3) y! + 2 cost y = 2 .53) and hence y = z1/4 = 1 + 15e2!2t Exercises (1) t 2 y! + 3ty = sin t .52) From the initial condition z(1) = 16 . y(" ) = 0.
His younger brother Johann also began to study mathematics at about this time. Bernoulli was appointed professor of mathematics in 1687. properties of curves including parabolas.!!y(1) = 2 t ans: y = 2 6 139t 18 ! 3t 17 (10) y! = t 2 y 2 " 4t 2 . his father ran a lucrative spice business. 1713). a studied the solution of the Bernoulli Differential Equation (1696). He married Judith Stupanus the following year and eventually had two children. Daniel (1700-1782) and Johann II (1710-1790) and Johann II’s sons Johann III (1744-1807) and Jacob II (1759-1789) was born into an influential Swiss family. He showed that the isochrone (a curve of constant rate of descent in a gravitational field) can be solved with a first-order nonlinear differential equation (1689). and probability and games of chance (published posthumously. and his mother came from a family of bankers. and spirals and lemniscates (1692-1694). He traveled as a tutor. probability (1685). He attended the University of Basel. his brother Johann (1667-1748). © 2005 BE Shapiro [Math 351 Spring 2005 revised 3/25/05] Page 5. developed the technique of separation of variables and used the word “integral” in calculus for the first time (1690). found a method to keep a drawbridge balanced (1695).3 (9) y! " y = 4y "5 . several works on infinite series (1682-1704). studying with the leading mathematicians of Europe including Boyle and Hooke. (b) Show that w!(t) = "[q(t) + 2r(t)u(t)]w(t) " r(t) Historical Notes Jacob (Jacques) Bernoulli (1654-1705) was the first member of the great Bernoulli family to study mathematics (including his nephew Nicolaus (1662-1716). Johann was jealous of his brother and become one of his greatest critics. geometry (1687). eventually being dismissed from the University and leading to a total breakdown in sibling relations by 1697. Jacob Bernoulli’s contributions to mathematics include a study of logic and algebra (1685).10 . epicycloids. evolutes. was a magistrate and member of the Basel town council. finally returning to teach mechanics at the University of Basel in 1683. neither of whom studied mathematics. first in Geneva and later in France. Suppose that we already know one particular solution u(t). (a) Show that a more general solution is given by v(t)= u(t) + 1 w(t) for some function w(t). and the law of large numbers (1689). !!y (11) dy 1 = y dt e ! t ( 3 3/ 4 = 2 ) 1+ e 1" e ans: y = !2 coth(2t 3 / 3) ans: y = ln !t ± t 2 + C # " $ ecos y (12) y! = cos y te sin y + y (13) Ricatti's equation is y! = p(t) + q(t)y + r(t)y 2 . Johann’s sons Nicolaus (1695-1726). receiving a master’s degree in philosophy (1671) and a licentiate in theology (1676).